Electrospun FeS nanorods with enhanced stability as counter electrodes for dye-sensitized solar cells. (1st March 2017) - Zhang, Chenle; Deng, Libo; Zhang, Peixin; Ren, Xiangzhong; Li, Yongliang; He, Tingshu
Abstract: The performance of dye-sensitized solar cells (DSSCs) is strongly influenced by the catalytic performance of counter electrode (CE) materials. Platinum (Pt) is extensively used as the CE for DSSC, but the high cost and low resistance to corrosion of Pt-based CE material restricts its practical application. Herein, we prepared α-Fe2 O3 and FeS nanorods (NRs) through electrospinning and investigated their valence states using Mössbauer spectroscopy and also assessed their catalytic performances as CE materials. It was found that upon the conversion of n-type semiconductor α-Fe2 O3 into p-type semiconductor FeS through the sulfurization process, the photoenergy conversion efficiency (PCE) was increased from 3.79% to 6.47% which is comparable with Pt. This increment might be related to the higher amount of electron-hole pairs and higher electrical conductivity, as well as the mixed valence of Fe element in the iron sulfide which can facilitate the transfer of electrons to the electrolyte. Furthermore, the FeS NRs show a much better long-term stability than Pt due to the interconnected conductive paths and excellent mechanical stability endowed by the one-dimensional morphology.